Edukasi GEMBUS (Gerakan Makan Buah dan Sayur) untuk Siswa di SDN Mulyorejo I Surabaya - Febriani, Nur Rahma; Syahrul, Fariani; Ludita, Mirza; Prabasanti, Mezaluna; Prameswari, Ambarsih; Syahril, Shakila Aliyahputri; Pasaribu, Anggi Prabawa; Widyadhana, Engrasia; Syahrani, Aulia Izza; Zhafira, Dinda (Universitas Nurul Jadid, 2024)
Abstract. A lack of fruit and vegetable intake can increase the risk of malnutrition and obesity, which contribute to the prevalence of non-communicable diseases such as coronary heart disease, stroke, hypertension, and diabetes mellitus. Among elementary school children, a significant factor is the lack of awareness about the importance of consuming these foods. The GEMBUS (Movement for Eating Fruits and Vegetables) educational activity conducted at SDN Mulyorejo I Surabaya used visual, audio, and audio-visual media to address the awareness issue regarding the importance of consuming fruits and vegetables. This activity targeted students from classes 5A and 6A during the 2022/2023 academic year, with a total of 71 students. The objective of the GEMBUS education was to increase knowledge about the importance of consuming fruits and vegetables. The Wilcoxon test was used to determine the difference between the pre-test and post-test results. With a p-value of 0.000 (α<0.05), the study concluded that the GEMBUS educational activity successfully achieved its goal of raising awareness about the importance of fruit and vegetable consumption among the target group.